2002
DOI: 10.1177/030089160208800216
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Adenocarcinoma Associated with Granulomatous Gastritis. Case Report and Review of the Literature

Abstract: To the best of our knowledge this is the fourth example of gastric adenocarcinoma and granulomatous gastritis. These cases suggest an association between granulomatous gastritis and early gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
(1 reference statement)
0
6
1
1
Order By: Relevance
“…Some authors have found a better prognosis in some tumors [20][21], while others have not [22]. As we did not find a report concerning their presence in PDAC, some cases with favorable outcomes of granuloma associated with signet ring cell gastric carcinoma, which have also prominent desmoplasia, had been reported [23][24]. Macrophage attraction to tumoral sites is induced by the secretion of chemokines in the milieu, such as chemokine (C-C motif) ligand 5 (CCL5), which also has a role in granuloma formation [25].…”
Section: The Siege Strategycontrasting
confidence: 62%
“…Some authors have found a better prognosis in some tumors [20][21], while others have not [22]. As we did not find a report concerning their presence in PDAC, some cases with favorable outcomes of granuloma associated with signet ring cell gastric carcinoma, which have also prominent desmoplasia, had been reported [23][24]. Macrophage attraction to tumoral sites is induced by the secretion of chemokines in the milieu, such as chemokine (C-C motif) ligand 5 (CCL5), which also has a role in granuloma formation [25].…”
Section: The Siege Strategycontrasting
confidence: 62%
“…7 8 It has also been observed in breast, gastric, colonic and laryngeal cancer along with head and neck cancer. [9][10][11] However, literature reporting such non-specific granulomatous inflammation, namely sarcoid reaction in lung cancer, is limited. 4 5 12-14 Most of the reports describe sarcoid-like lymphadenopathy in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric granulomas may also occur in association with adenocarcinomas and mucosa‐associated lymphoid tissue (MALT) lymphomas 96 . In the former, they appear to be an inflammatory response to invasive tumour or extravasated mucin, similar to what has been described at other sites.…”
Section: Miscellaneous Forms Of Gastritis With a Distinctive Histologymentioning
confidence: 83%